2014
DOI: 10.1021/jo500780b
|View full text |Cite
|
Sign up to set email alerts
|

Metal-Free Protodeboronation of Electron-Rich Arene Boronic Acids and Its Application to ortho-Functionalization of Electron-Rich Arenes Using a Boronic Acid as a Blocking Group

Abstract: The metal-free thermal protodeboronation of various electron-rich arene boronic acids was studied. Several reaction parameters controlling this protodeboronation, such as solvent, temperature, and a proton source, have been investigated. On the basis of these studies, suitable reaction conditions for protodeboronation of several types of electron-rich arene boronic acids were provided. On the basis of this protodeboronation, a new protocol for the synthesis of ortho-functionalized electron-rich arenes from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
32
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 32 publications
1
32
0
Order By: Relevance
“…This could due to the lack of reactivity of the boronate esters (Bpin) when compared to the free boronic acid derivatives or due to mechanistic reasons in some cases . We found an isolated single example wherein N , N ‐dimethylaniline functionalized with −Bpin at the para ‐position, when subjected to C−H nitration using AgNO 3 and NBS, predominantly produced the ipso ‐nitration product instead of the desired isomer . However, when we subjected these conditions to the crude boronate obtained from the iridium‐catalyzed reaction, the reaction failed with no traces of the desired product.…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…This could due to the lack of reactivity of the boronate esters (Bpin) when compared to the free boronic acid derivatives or due to mechanistic reasons in some cases . We found an isolated single example wherein N , N ‐dimethylaniline functionalized with −Bpin at the para ‐position, when subjected to C−H nitration using AgNO 3 and NBS, predominantly produced the ipso ‐nitration product instead of the desired isomer . However, when we subjected these conditions to the crude boronate obtained from the iridium‐catalyzed reaction, the reaction failed with no traces of the desired product.…”
Section: Methodsmentioning
confidence: 98%
“…[10d] We found an isolated single example wherein N,N-dimethylaniline functionalized with ÀBpina tt he paraposition, when subjected to CÀHn itration using AgNO 3 and NBS, predominantly produced the ipsonitration product instead of the desired isomer. [14] However,w hen we subjected these conditions to the crude boronate obtained from the iridium-catalyzed reaction, the reaction failed with no traces of the desired product. Later,w es tarted at horough investigation of conditions for converting the crude boronates obtained by the CÀHb orylation of arenes to nitroarenes using coppercatalysis.…”
mentioning
confidence: 99%
“…9 Alternatively, electron-rich boronic acids can be deborylated using water or acetic acid as the proton source. 10,11 In these chemistries, the boronic ester or acid can be used for site-specific deuteration or as a blocking group that enables regioselective bromination. These features are summarized in Scheme 1.…”
Section: Introductionmentioning
confidence: 99%
“…Reaction of the hydrazone 3 with the diortho-substituted boronic acid 2 could lead to avrainvilleol after removal of the methyl ethers. Alternatively, hydrazone 4 and known boronic acid 5 could be merged to give rise to 1 . Preliminary and subsequent reports of these hydrazone/boronic acid couplings revealed that a single ortho-, meta-, or para-substituent was well tolerated in either the hydrazone or boronic acid coupling partner.…”
mentioning
confidence: 99%